Penciptaan Desain Karakter Tokoh Mitologi Asal Usul Suku Batak dengan Menggunakan Artstyle Manga Seinen - Chensin Agnes Lidya Sihotang; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This creation aims to design characters based on mythological figures from the origin story of the Batak tribe using the visual approach of the seinen manga art style. Batak mythology, which is rich in cultural values and ancestral narratives, is explored through a visual style that resonates with contemporary audiences. The seinen manga style is chosen due to its realistic, emotional, and thematically mature characteristics, making it appropriate for depicting traditional myths without diminishing the respect for cultural beliefs and values. The methods applied in this character design process include literature studies on Batak mythology, visual analysis of the seinen manga style, and concept exploration through stages of digital art creation. The main characters depicted are Debata Bataraguru, Debata Soripada, and Debata Mangalabulan, accompanied by traditional attributes that represent the cultural values of the Batak tribe.